2003
DOI: 10.1117/12.499026
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced thermal characterization of nano Ag metal dispersed ceramic alumina matrix

Abstract: In this paper, we report the measurements of thermal diffusivity of nano Ag metal dispersed ceramic alumina matrix sintered at different temperatures using laser induced non-destructive photoacoustic technique. Measurements of thermal diffusivity also have been carried out on specimens with various concentration of nano metal. Analysis of the data is done on the basis of one-dimensional model of Rosencwaig and Gersho. The present measurements on the thermal diffusivity of nano metal dispersed ceramic alumina s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Thus, lattice connectivity is enhanced, the scattering centres are reduced and the mean free path is increased. This increase in mean free path of heat carrier results in an increased value for TD of the sintered samples [9,50]. Table 2) also show the same trend as the non-sintered ones [14].…”
Section: Philosophical Magazine 901supporting
confidence: 65%
See 1 more Smart Citation
“…Thus, lattice connectivity is enhanced, the scattering centres are reduced and the mean free path is increased. This increase in mean free path of heat carrier results in an increased value for TD of the sintered samples [9,50]. Table 2) also show the same trend as the non-sintered ones [14].…”
Section: Philosophical Magazine 901supporting
confidence: 65%
“…But, it is observed that the TD of MB-5 is less than that of K-10. The higher TD of K-10 can be due to the enhanced lattice connectivity [9,49,50]. Here, also, we can see that the repeatedly adsorbed sample has a lesser TD than the single adsorbed sample, which may be due to the densely packed dye molecules, as in the case of the non-sintered samples.…”
Section: Philosophical Magazine 901mentioning
confidence: 56%